2020
DOI: 10.5195/aa.2020.314
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Care, and Isolation in the Time of COVID-19.

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The narratives of the older adults indicated that they were unhappy with the state government of West Bengal which had failed to provide for their daily needs. Similar to the studies conducted by Manderson and Levine (2020) and Clotworthy and Westendorp (2020) in South Africa and Denmark, the policies of the Government of India further isolated and created more challenges for the elderly population in urban India.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The narratives of the older adults indicated that they were unhappy with the state government of West Bengal which had failed to provide for their daily needs. Similar to the studies conducted by Manderson and Levine (2020) and Clotworthy and Westendorp (2020) in South Africa and Denmark, the policies of the Government of India further isolated and created more challenges for the elderly population in urban India.…”
Section: Discussionmentioning
confidence: 64%
“…Contradicting the image of the vulnerable, isolated and dying elderly during the pandemic, Lamb argues that older Americans were also experiencing vibrant social connections, agency and pleasure during the lockdown. Highlighting the situation of the elderly with comorbidities in South Africa, Manderson and Levine (2020) in their study illustrate that the pandemic amplified already existing structural vulnerabilities in the care arrangement systems for the frail and aged in South Africa. Findings from their study indicated that while the pandemic heightened social isolation for the elderly in the wealthier households, it increased levels of dependency and vulnerability in poorer households.…”
Section: Studies On the Pandemic And The Elderly: A Global Perspectivementioning
confidence: 99%
“…This is not to say that the COVID-19 pandemic has not been a radical event with serious long-term consequences. The suspension of public and private home-care services, as well as semi-residential services such as adult day-care centers, increased social inequalities and posed serious threats to older people and their family in Italy and elsewhere (Kent et al 2020;Manderson and Levine 2020). And yet, before the COVID-19 pandemic in Italy, like many places in the so-called Euro-American area, the general assumption had been that modern medical technologies have succeeded in defeating the infectious diseases of the past, and have given us the opportunity to live a long life.…”
Section: Discussionmentioning
confidence: 99%
“…This exclusion criterion allowed us to focus on the OHT's implementation of the plans outlined in the full application. While we realize that the pandemic was of great significance, it is also important to ensure that the OHTs are not pausing the work they set out to accomplish, such as increasing resources for mental health and addictions or improving transitions care of the elderly, prior to the declaration of the pandemic [17,18]. In fact, integrated care with strong partnerships is even more significant during this time [19].…”
Section: Inclusion/exclusion Criteria For Google Searchmentioning
confidence: 99%